A magyar külpolitika válságkezelő kísérletei a nagy gazdasági világválság idején Bethlen István és Károlyi Gyula kormányai alatt (1929-1932) - Vizi, László Tamás (Közép-Európai Közlemények, 2015)
The Great Depression that broke out on 24th October 1929 resulted a severe agricultural and credit crisis in Hungary. Therefor the Hungarian foreign policy’s aim was to encourage the foreign investments on the one hand, and to circulate loans for the country ont he other hand, and last but not least obtain foreign markets for the Hungarian agricultural products. The present study summarize the attempts of the Hungarian foreign policy between 1929 and 1932, that the Hungarian government led by István Bethlen and Gyula Károlyi trying to achieve in order to overcome the crisis. The study describes Bethlen’s negotiations in Paris, London, Berlin, Vienna, that brought part success, but did not result a breakthrough and Hungary’s external action concerning the German-Austrian customs union plan. It presents the two foreign ministers Lajos Walko’s and Gyula Karolyi’s attempts. Concerning Gyula Károlyi is about the Hungarian foreign policy’s French orientation attempt. Finally, the study summarize the reasons that ultimately led to the failure of both governments. Finding the foreign policy solution for recovering from the crisis left for the 1932 October founded government and for Gyula Gombos.